PENGARUH RELIGIOSITAS TERHADAP PENCIPTAAN BISNIS: PERAN PEMEDIASI ORIENTASI KEWIRAUSAHAAN INDIVIDU DAN SIKAP BERBAGI PENGETAHUAN - Muhammad Hamdi; Rikha Muftia Khoirunnisa (Jurnal Fokus Manajemen Bisnis, 2022)
The purpose of this study was to examine the role of individual entrepreneurial orientation and knowledge-sharing attitudes on the influence of religion on the creation of new businesses. Data were collected from 300 millennial and post-millennial generations in Yogyakarta. Regression analysis with bootstrap method was used to test the hypothesis. The results prove that religiosity has a positive effect on the creation of new businesses, individual entrepreneurial orientation mediates the effect of religiosity on the creation of new businesses, and knowledge sharing attitudes mediate the effect of new business creation. The limitation of this study lies in the ability to explain the variations and dynamics of the new business creation process that differs from the identified stages.